Islamic Adoptional Jurisprudence versus Best Interest Principle with Special Reference to Minor Child in India - Shaikh, Anisa; Dubey, Rashmi (International Journal of Psychosocial Rehabilitation, 2020)
In Muslim law, the child is considered as legitimate only if the father of child proves the acknowledgement of his child otherwise child will not be considered as the natural child of that person. Quran also relates the relevant text about the consequences of adoption. Under Islamic law the relationship between orphaned child and the guardian is different from other personal laws. Muslim laws recognize the acknowledgment of paternity and establish the legitimacy of child. However the Supreme Court has extended right to Muslims through its outstanding pronouncement in 2014. Supreme Court held that restrictions placed by personal law i.e. Muslim law should not come in the way of citizen’s right to adopt a child. Personal beliefs do not dominate the law of land of country.